Nutrient content of selected wild edible mushrooms from Braha-kshetra Community Forest, Dang, West Nepal (Botanica Orientalis: Journal of Plant Science, 2025)
In the present study, four wild edible mushrooms (Laccaria laccata, Lactarius volemus, Russula delica, and R. poichilochroa) from Ghorahi, Dang, west Nepal were analyzed for nutrient and mineral contents. The moisture content of mushrooms varied from 5.16 to 5.51%, protein from 24.28 to 24.59%, fat from 2.20 to 2.97%, ash from 11.25 to 15.16%, and carbohydrates from 58.37 to 61.28%. The mineral content ranged 1.13–2.00 µg/g for Ca, 0.90–1.03 µg/g for Mg, 25.99–100.37 µg/g for Mn, 1.03–2.87 µg/g for Fe, 3.06–3.36 µg/g for K, 16.83–17.94 µg/g for Cu, 2.17– 4.87 µg/g for P, and 39.61–60.56 µg/g for Zn. Russula delica exhibited a high amount of moisture, carbohydrates, and protein, followed by Lactarius volemus and Russula poichilochroa, whereas Laccaria laccata had the least amount of nutrients, except for ash. However, minerals such as Mn, Zn, Fe, P, Mg, and K were present in higher amounts in L. laccata, followed by Lactarius volemus, Russula poichilochroa, and R. delica. In conclusion, the four species of mushrooms can be used as important nutrient sources due to their high protein, carbohydrate, and mineral contents.